Efektifitas Mathmagic dalam Peningkatan Hasil Belajar Matematika - Ari Irawan; Chatarina Febriyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2016)
This study aims to determine the effectiveness of the use of mathmagic on learning outcomes of mathematics at elementary school. The method used in this study is the experimental method is to provide treatments or treatment in the study sample. Where will compare between pretest and posttest. Research hypothesis testing by means of the t test are two different test average. After a study found 0,012 results <0.05 it can be concluded there is an average difference between before and after treatments. With the correlation value of 0.494, which means strong enough or the coefficient of determination 24.41%. With the value of effectiveness when compared between before and after treatments amounted to 90.42%. Keywords: Effectiveness, Mathmagic, Results Learning Mathematics, Elementary School